Challenges with Density-Based Grade Estimation at LKAB’s Underground Iron Ore Mines - Manzoor, Sohail; Gustafson, Anna; Schunnesson, Håkan (Mining, Metallurgy & Exploration, 2022)
Sublevel caving operation relies on the estimation of ore grade at drawpoints, as the mine management uses grade to decide whether the material at a certain ring should be loaded or abandoned. Grade is estimated in various ways, including visual estimation, density-based calculation, and sampling and assay methods. The grade estimation at the world’s two largest underground iron ore mines owned by LKAB in northern Sweden is based on the density difference between ore and waste. The calculations assume a constant swell factor, a theoretical fill of 100%, and a linear relationship between bucket weight and material grade. This study evaluated these assumptions in detail based on the loading data for 12,237 buckets and concluded that the method has some shortcomings which render the assumptions invalid. Further research is required to deal with these shortcomings to improve estimation of the material grade. Validerad;2022;Nivå 2;2022-12-06 (joosat); Funder: Luossavaara-Kiirunavaara AB (LKAB)